Experimental Evaluation of the Mechanical Properties of Geopolymer Concrete Using Recycled Coarse Aggregates from Construction Waste - Pengki Suanto; Mulyadi Sugih Dharsono (Riviera Publishing, 2026)
The rapid growth of construction and demolition activities has significantly increased the generation of construction waste, with concrete waste representing the largest proportion. This study aimed to investigate the effect of Recycled Concrete Aggregate (RCA) as a partial replacement for natural coarse aggregate on the compressive strength of fly ash-based geopolymer concrete and to determine the optimum RCA content that provides the best mechanical performance. This research employed a laboratory experimental design with RCA replacement levels of 0%, 25%, 50%, 75%, and 100% by weight of coarse aggregate. The geopolymer binder was produced using fly ash activated with an alkaline solution consisting of sodium hydroxide (NaOH) and sodium silicate (Na?SiO?) at a 2:1 ratio. Tests for compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity were conducted after 28 days of curing in accordance with applicable ASTM standards. The results showed that RCA incorporation improved the compressive strength of geopolymer concrete up to an optimum replacement level. The compressive strength values obtained for RCA replacement levels of 0%, 25%, 50%, 75%, and 100% were 25.98 MPa, 26.65 MPa, 30.21 MPa, 24.25 MPa, and 23.91 MPa, respectively. The highest compressive strength was achieved at 50% RCA replacement, representing an increase of approximately 16.3% compared with the control mixture. However, further increases in RCA content resulted in reduced strength due to increased porosity, higher water absorption, and the presence of residual mortar attached to recycled aggregates. These findings indicate that a 50% RCA replacement level represents the optimum proportion for producing sustainable fly ash-based geopolymer concrete with enhanced compressive strength and environmental benefits.